IMPLEMENTASI RESTORATIVE JUSTICE DALAM TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENYEBABKAN LUKA RINGAN (Studi Kasus Di Kejaksaan Negeri Kota Kediri) - Anandi, Normalita Rauffadilla; Handayani, Emi Puasa; Chasanah, Nur; Ferbriana, Maria; Artantojati, Sigit (Universitas Islam kadiri, 2024)
An unplanned and unintentional event involving a vehicle that results in loss can occur in a traffic accident with or without other road users. Road accidents have legal consequences for the perpetrator or the cause of the occurrence, which can be in the form of punishment or even prosecution. compensation for material losses actually suffered.The formulation of the problem of this research, How is the implementation of restorative justice in the criminal act of traffic accidents that cause minor injuries? and How are the obstacles or obstacles in the implementation of restorative justice in the criminal act of traffic accidents that cause minor injuries? By using restorative justice, this study seeks to determine the role of the prosecutor's office in handling criminal traffic accidents on behalf of the community. The District Attorney of Kediri City conducted empirical research as part of the methodology used in this study. The purpose of this research is to find out how, in accordance with Perja No. 15/2020, restorative justice is provided to perpetrators of traffic accidents at the stage of termination of prosecution. In addition, it aims to find out the challenges faced by the Kediri City District Attorney's Office in applying restorative justice to perpetrators of traffic accident crimes.